FORECASTING OF AMBON CITY CONSUMER PRICE INDEX (CPI). USING DOUBLE EXPONENTIAL SMOOTHING METHOD FROM BROWN - Istifarin, Nadia; Van Delsen, M. S. Noya; Djami, R. J. (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2023)
The Consumer Price Index (CPI) is an index that measures the average price of goods and services consumed by households in a certain period of time. An increase in the CPI can cause an increase in interest rates, increase the growth of the money supply, increase the attractiveness of the currency, and increase inflation. The results of the visualization show that the Ambon city CPI forms a trend pattern. This study aims to predict the Ambon CPI from January 2022 to June 2022 using Brown's double exponential smoothing method. The results of the analysis show that the best parameter for forecasting the CPI value of Ambon city is α=0.7 with a MAPE value=1.2644%, which obtains successive forecast results are January at 110.5908, February at 111.4186, month March was 112.2389, April was 113.8871, May was 113.8871 and June was 14.7112. These results show that the CPI forecast for Ambon City has increased every month.